An Error Analysis Of Pronouncing English Diphthongs (International Journal of Education and Literature, 2023)
Pronunciation plays an important role in communication. It provides the different meaning of English words when they are pronounced differently especially English diphthongs. Producing errors in pronouncing English diphthongs cause misunderstanding in communication. The research was aimed to know(1) the commonmispronounced diphthongs by the second semester of English Study Program’s students atintermediate speaking class and (2) the causation of errors in pronouncing English diphthongs. The mixed method research was used to get the data. The qualitative data were taken based on the observations, documentations, and interviews, meanwhile the quantitative data were taken based on the errors of the students on the tests. The results of the research were described by the percentages. The students commonly made diphthong errors as follows/uә/= 19.3%, /eә/= 21.3%, /ei/= 20%,/aʊ/= 13.10%, and/ɪә/= 26.2%.The errors happened in the classifications ofsubstitution = 46.9%, insertion = 13.8%, and omission = 39.3%. It happened because of the influence of inter-lingual and intra-lingual factors.